2014
DOI: 10.4141/cjas2013-185
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis and stochastic simulation of alternative beef calving and feeding systems in western Canada

Abstract: Khakbazan, M., Carew, R., Scott, S. L., Chiang, P., Block, H. C., Robins, C., Durunna, O. N. and Huang, J. 2014. Economic analysis and stochastic simulation of alternative beef calving and feeding systems in western Canada. Can. J. Anim. Sci. 94: 299–311. Biological and economic data from three field-experimental sites in Manitoba (Brandon Research Centre) and Saskatchewan (Western Beef Development Centre; Semi-Arid Prairie Agriculture Research Centre) were used to determine the economic and financial benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…However, the beef system that a producer would choose or adopt cannot solely be evaluated by the CDF analytical framework, as each individual producer may have different risk preferences. Therefore, as reported by Khakbazan et al (2014), the concept of SERF is a more preferred analytical technique.…”
Section: Distribution Function Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the beef system that a producer would choose or adopt cannot solely be evaluated by the CDF analytical framework, as each individual producer may have different risk preferences. Therefore, as reported by Khakbazan et al (2014), the concept of SERF is a more preferred analytical technique.…”
Section: Distribution Function Approachmentioning
confidence: 99%
“…3). Khakbazan et al (2014) assumed 98% calfweaning rate and also used different price data and reported that the LC system was a preferable option. Assuming a 98% weaning rate for both EC and LC in this study also indicated that the LC system resulted in higher returns than the EC system throughout the range of alternative return distributions analyzed in all sites (data not shown).…”
Section: Distribution Function Approachmentioning
confidence: 99%
See 3 more Smart Citations